Partnership Pattern in Bali Cattle Risk Management in Purification Cluster Area - Siregar, Ahmad Ramadhan; Astaman, Putra; Munizu, Musran; Hastang; Dassir, Muhammad; Hikmah, Aulia Nurul; Darwis, Muhammad (Program Studi Agribisnis Universitas Muhammadiyah Sinjai, 2024)
Agricultural businesses, including beef cattle farming, are prone to risks and losses. Partnerships provide many benefits and reduce the risk of business losses through market assurance, added value, and an increased portfolio of productive assets. The Bali cattle cluster is a place of centralized development in cattle breeding to enhance high competitiveness. The study aims to build a partnership model for managing the risk of the Bali cattle business in the Bali cattle purification cluster. The research used a survey method with a descriptive qualitative approach. The results showed two partnership models in the research location: the partnership of the livestock company and the traditional partnership. Business cooperation is established in partnership with farmers by dividing profits among 50% farmers, 45% companies, and 5% farmer-livestock groups. As for traditional partnerships, farmers and owners get 50% of the profits each. So, the two business models of beef cattle farming have advantages and disadvantages. The partnership system has a good impact on farmers in managing their business risks because farmers feel helped by these two partnerships in the research location, especially for farmers who still have minimal business capital in the Bali cattle business. Future research will be maximized if it increases the number of respondents and the size of the research area to detect agricultural partnership patterns in rural areas.